2012
DOI: 10.1002/jbio.201200088
|View full text |Cite
|
Sign up to set email alerts
|

Nanodiamond for intracellular imaging in the microorganisms in vivo

Abstract: Nanodiamond (ND) has great potential for bio labeling and drug delivery. In this work, the biocompatibility and bio labeling of ND are demonstrated via the interaction with cells and microorganisms, protists microorganisms Paramecium caudatum and Tetrahymena thermophile, in vitro and in vivo. We found the microorganism's living functions are not significantly affected by ND. The NDs were found entering the food vacuoles and later excreted by the microorganisms. The 5 nm ND was found more toxic compared to 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 40 publications
0
35
0
Order By: Relevance
“…[5][6][7][8][9][10][11][12][13] Recently, ND has been shown to be a highly biocompatible drug carrier. [14][15][16][17][18][19][20][21][22][23] Being a sp 3 carbon based material, the surface property of ND is quite different from its sp 2 counterparts. While remarkable progresses have been made on the application side, fundamental interactions at the bio/nano interface are still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13] Recently, ND has been shown to be a highly biocompatible drug carrier. [14][15][16][17][18][19][20][21][22][23] Being a sp 3 carbon based material, the surface property of ND is quite different from its sp 2 counterparts. While remarkable progresses have been made on the application side, fundamental interactions at the bio/nano interface are still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Smaller DNDs show higher toxicity toward human cells than larger HPHT NDs (Fig. 6), evidenced by effects on cell viability, proliferation, apoptosis and metabolic activity Thomas et al 2012;Lin et al 2012;Chao et al 2007;Burleson et al 2009). This phenomenon can be explained not only by the different sizes (and surface areas) of the particles but also by the presence of reactive disordered carbon structures on the surfaces of DNDs, which contrasts with the highly ordered (and oxidized) sp 3 carbons on HPHT NDs Lin et al 2012).…”
Section: Comparative In Vitro Biocompatibility Studies Of Different Nmentioning
confidence: 93%
“…The comparative toxicities of different ND types have been intensively studied Thomas et al 2012;Lin et al 2012;Chao et al 2007;Burleson et al 2009). ND toxicity depends on many factors, including production process, concentration and incubation time.…”
Section: Comparative In Vitro Biocompatibility Studies Of Different Nmentioning
confidence: 98%
“…Lin et al 52 reported that NDs of~140 nm in size could enter the food vacuoles of the microorganisms but later were excreted. Interestingly, the biological functions (such as cell division) of the living unicellular organisms were not significantly affected by the presence of NDs.…”
Section: Nanodiamonds As Bioimaging Agents Wide-field Fluorescence Immentioning
confidence: 99%